FENOMENA NILAI TUKAR RUPIAH PADA DOLLAR AMERIKA - Putu Diah Putri Idawati (STIMI Handayani Denpasar, 2016)
International trade will lead to differences in the currency used by thecountries concerned. The determination of the exchange rate system is an importantthing for the economy of a country because it is a tool that can be used to stimulatethe economy in a state of global economic turmoil. Indonesia as a country with asmall open economy has experienced some exchange rate system replacement. Thisstudy analyzes intended as a material in order to deepen knowledge about issues thataffect the rise and fall of the rupiah to the US dollar. The results of this study showedsome factors that influence the rise and fall of the exchange rate on the US dollar,namely the difference in inflation rates, the difference in interest rates, capital flight(capital flight), political instability and economic, export prices and import prices,public debt, the amount of money circulating, recession and speculation.